2022
DOI: 10.1186/s13018-022-03291-2
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression profile for the lower osteogenic potent of bone-derived MSCs from osteoporosis with T2DM and the potential mechanism

Abstract: Background Osteoporosis (OP) patients complicated with type II diabetes mellitus (T2DM) has a higher fracture risk than the non-diabetic patients, and mesenchymal stem cells (MSCs) from T2DM patients also show a weaker osteogenic potent. The present study aimed to provide a gene expression profile in MSCs from diabetic OP and investigated the potential mechanism. Methods The bone-derived MSC (BMSC) was isolated from OP patients complicated with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Long-term BMSC cultures in high glucose have been shown to exhibit decreased differentiation capability without indication of senescence ( Al-Qarakhli et al, 2019 ). Xia et al (2022) studied BMSCs from osteoporotic patients with or without T2DM using RNA-seq and noticed that T2DM-derived BMSCs exhibit decreased differentiation and mineralization capacity, which they attributed to attenuated expression of Forkhead Box Q1 (FOXQ1). However, we did not observe changes in FOXQ1 in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term BMSC cultures in high glucose have been shown to exhibit decreased differentiation capability without indication of senescence ( Al-Qarakhli et al, 2019 ). Xia et al (2022) studied BMSCs from osteoporotic patients with or without T2DM using RNA-seq and noticed that T2DM-derived BMSCs exhibit decreased differentiation and mineralization capacity, which they attributed to attenuated expression of Forkhead Box Q1 (FOXQ1). However, we did not observe changes in FOXQ1 in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…As a nucleic acid binding protein, FOXQ1 can inhibit the replicative senescence by decreasing the levels of IL-6 and IL-8 via modulation of the SIRT1-NFκB pathway [ 39 ], and the FOXQ1-ANXA2 complex can promote the Wnt/β-catenin pathway in bone MSCs, thereby leading the osteogenic differentiation subsequently [ 40 ]. In addition, Xia et al have found that silencing of FOXQ1 significantly inhibits the osteogenic differentiation of bone-derived MSCs from osteoporosis with T2DM [ 25 ]. Based on the previous study results, FOXQ1 could be seen as a chondrocyte biogenesis factor in osteogenesis, but the role of FOXQ1 in cartilage degradation of OA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are widely employed in traumatic tissue repair, immune disorders, and cancer therapy. The proliferative capacity and immunogenicity of MSCs from different human populations vary greatly, and the osteogenic potential of MSCs derived from diabetic patients is decreased than health volunteers[ 18 ], while MSCs isolated from patients with autoimmune diseases have morphological and some functional abnormalities[ 19 ], which implies that the normal MSCs transplants may restore the MSCs function and alleviate the disease.…”
Section: Scope and Benefits Of Mscs In Clinical Utilizationmentioning
confidence: 99%